THE CONVERGENCE OF PSYCHOLOGY AND TECHNOLOGY: ENHANCING MENTAL HEALTH AND WELL-BEING (The Research of Medical Science Review, 2024)
This paper explores the intersection of psychology and technology, focusing on their combined effects on mental health and well-being. As digital tools and platforms become increasingly integrated into daily life, they offer new avenues for mental health support, including online therapy, mental health apps, and virtual support communities. However, the study also addresses potential challenges, such as the impact of social media on self-esteem and the risks of technology addiction. By analyzing current trends and empirical research, this work aims to highlight both the benefits and drawbacks of technological advancements in mental health care. Ultimately, it advocates for a balanced approach that leverages technology to enhance psychological well-being while mitigating its adverse effects.